PENGUMPAN (SETTER) SEBAGAI JANTUNGNYA PERMAINAN OLAHRAGA BOLA VOLI - Fauzi Fauzi (Departement of Sports Coaching, Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2016)
Setter is an important player in volleyball games. Quality of setter is determined quality of whole volleyball player performance. Furthermore, we can make a justification if the successfully of volleyball teams depend on setter conditions. Passing technique of setter in volleyball games is influenced by ready position, impact, and follows throw. Recently, passing technique setter is getting becomes various, such as quick ball, open ball, straight, etc. A good setter is somebody who has ability to choose which one of kind of ball passing that appropriate to apply in some conditions. It is the main factor of volleyball teams to be a winner. Keywords: Setter, volleyball, main factor.